The art of the start 2.0 : the time-tested, battle-hardened guide for anyone starting anything - Kawasaki, Guy, 1954- (Tantor Media, 2015)
Whether you're an entrepreneur, intrapreneur, or not-for-profit leader, there's no shortage of advice on such topics as writing a business plan, recruiting, raising capital, and branding. In fact, there are so many books, articles, and Web sites that many startups get bogged down to the point of paralysis, or they focus on the wrong priorities and go broke before they discover their mistakes. The Art of the Start 2.0 solves that problem by distilling Guy Kawasaki's decades of experience as one of the most original and irreverent strategists in the business world. Since late 2004, The Art of the Start has been the essential guide for anyone starting anything, from a multinational corporation to a church group. From raising money to hiring the right people, from defining your positioning to creating a brand, from driving buzz to buzzing the competition, this book will guide you through an adventure that's more art than science-the art of the start.